PENGARUH EKSTRAK ETANOL DAGING BEKICOT (Achantina fulica) TERHADAP KADAR KOLESTEROL TOTAL, HDL, DAN LDL SERUM DARAH TIKUS JANTAN GALUR WISTAR - Widyaningsih, Wahyu; Prabowo, Aditya; Sumiasih, Sumiasih (Universitas Andalas, 2010)
Cholesterol was a steroidal compounds contained in the human body. Cholesterol imbalance in the body caused hypercholesterol disease. Acharan sulfate is a compound found in snail body and potentially lowering cholesterol level. Acharan sulfate was extracted from snail body with maceration method using ethanol solvents. Research was done by using animals model, male rats (Rattus norwegicus) Wistar strain which was two months old and weighing 180 to 200 grams. The animals model were divided into six groups. One groups used as normal control. Five groups were treated with high cholesterol diet with suspense of cow fat and yellow egg for ten days. After that, three groups were treated with the ethanolic extract of snail body with doses of 40 mg/kgbw, 80 mg/kgbw, and 160 mg/kgbw. The two other groups were treated with Simvastatin and BR II feed (disease control). Total cholesterol, HDL and LDL concentrations were determined using enzymatic photometric test CHOD-PAP method. Results showed that snail body the ethenolic extract of decreased total cholesterol concentration by 6,33 mg/dl at doses 160 mg/kgbw and 4,90 mg/dl at doses 80 mg/kgbw. HDL concentration increased by 0,85 and 8,06 mg/dl respectively at doses 80 mg/kgbw and 160 mg/kgbw. LDL concentration decreased by 1.96 mg/dl, 2.22 mg/dl and 3.52 mg/dl respectively at doses 40, 80, and 160 mg/kgbw.